2004
DOI: 10.1021/op034122y
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of 1,2-Diols by Enzyme-Catalyzed Oxidation with Anodic, Mediated Cofactor Regeneration in the Extractive Membrane Reactor:  Gaining Insight by Adaptive Simulation

Abstract: Oxidative racemic resolution of 1,2-diols is a method for the synthesis of enantiopure diols not easily accessed by reduction. The constraints generally found for oxidation to hydroxy ketones can be overcome by coupling various techniques. To circumvent product inhibition, a membrane reactor with solvent extraction of the lipophilic product was chosen. For the oxidative regeneration of NAD+ from NADH anodic oxidation mediated by ABTS was used. The kinetic characteristics of the system were determined independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Furthermore, it is not always possible to account for continuous conditions by kinetic investigations 19. 21 Catalysts suitable for continuous operation are chosen for stability reasons rather than for short‐lived activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is not always possible to account for continuous conditions by kinetic investigations 19. 21 Catalysts suitable for continuous operation are chosen for stability reasons rather than for short‐lived activity.…”
Section: Introductionmentioning
confidence: 99%
“…The cofactor NAD + was regenerated by anodic oxidation of NADH using ABTS (2,2¢-azinobis(3-ethyl-benzothiazolin-6-sulfonate) as the mediator [52]. Electrochemical oxidation, ultrafiltration, extraction and distillation were combined in one single system.…”
Section: Membranes In Bioelectrochemistrymentioning
confidence: 99%
“…The process utilises an enzymatic cofactor regeneration process catalysed by formate dehydrogenase . Cofactor regeneration based on enzymatic, electrochemical, chemical, and photochemical methods has been described, with enzymatic methods used most commonly . Enzymatic regeneration is widely used as it displays high selectivity and efficiency, however it requires the use of additional enzymes and substrates in order to regenerate the cofactor.…”
Section: Introductionmentioning
confidence: 99%
“…Kochius et al. [29] demonstrated that ABTS (2,2‐azino‐bis‐(3‐ethyl‐benzo‐thiazoline‐6‐sulfonic acid) is a highly efficient mediator for the regeneration of NADH with a high turnover factor (TF) of 1200 h −1 which compares very favourably with mediators such as methylene blue or methylene green (TF 75 h −1 and 25 h −1 respectively) . Moreover, ABTS can be easily used in large scale systems (i. e. reactors) because of its high stability in a broad range of conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation